Interaction between glutathione S‐transferase M1‐null/present polymorphism and adjuvant chemotherapy influences the survival of breast cancer - Shuang Li; Guan‐Tian Lang; Ying‐Zhou Zhang; Ke‐Da Yu; Zhi‐Ming Shao; Qiang Zhang (Cancer Medicine)
Abstract Glutathione S‐transferase M (GSTM) family is concerned with oxidative stress, which is associated with breast carcinogenesis and chemotherapy response. The null polymorphism of GSTM1 gene results in a thorough absence of the enzyme function. Our study was to evaluate the association between GSTM1 null/present polymorphism and chemotherapy treatment outcome in breast cancer patients. A total of unrelated 714 patients with a histologically confirmed breast cancer were randomly selected from two independent cancer centers. Polymerase chain reaction was performed to analyze null/present genotypes of GSTM1 in our study. Our study found that the present genotype of GSTM1 was associated with a better relapse‐free survival (RFS) (P = .03) with adjusted hazard ratio (HR) [95% confidence interval (CI)] of 0.63 (95% CI: 0.42‐0.93). The present genotype of GSTM1 was significantly correlated with a better RFS compared with the null genotype in the nonchemotherapy group (HR = 0.17, 95% CI: 0.06‐0.50; P = 0.001), but no effect was observed in the chemotherapy group (HR = 0.81, 95% CI: 0.52‐1.26; P = 0.35). Moreover, the interaction between the GSTM1‐null/present genotype and adjuvant chemotherapy was significant (P = 0.04) in further analysis. Our study suggests that the GSTM1 polymorphism plays a complex role in influencing the chemotherapy response and breast cancer survival. It is suggested that the GSTM1‐present genotype might prevent progression in breast cancer patients. In the meanwhile, it could damage the benefit of adjuvant chemotherapy as well in certain ways.